Evaluation of Status of Getting ill with SARS CoV-2 and the Knowledge of Using and Attitudes of Personal Protective Equipment at Pre-Hospital Emergency Care Services Employees - Hasan Kara; Fatma Sözen Özmen (Genel Tıp Dergisi)
Objective: The present study aimed to evaluate the knowledge level of health personnel working in pre-hospital emergency health services in the Konya province regarding the coronavirus disease 2019 (COVID-19) infection and the use of personal protective equipment (PPE) during the pandemic. Material and Methods: A total of 410 health personnel working in emergency health services in the Konya province were included in the study. The data were collected through a questionnaire developed by the researcher inquiring about the demographic data, whether they contracted (COVID-19), knowledge about COVID-19, and knowledge and attitudes regarding the use of PPE. Results: The rate of individuals who experienced mild infection was 27.1% and the rate of individuals who experienced severe infection was 5.6%. Of the subjects who experienced COVID-19 infection, 73.8% had fatigue, 67.9% had bone and muscle ache, 47.7% had fever, 42.5% had a cough and 27% had loss of taste, smell, and gastrointestinal symptoms and 25.3% had dyspnea. Of the health personnel, 83.7% were detected to use PPE. The most commonly used PPE was seen to be gloves (90.8%) and the least was visors and eyeglasses (43.8%). When the symptom frequency was analyzed according to age, the symptoms were found to be most frequent in the age group of 40 years and above and the symptom frequency was seen to increase with age. Conclusion: It was concluded that the health personnel had received in-service training about COVID-19 and had sufficient knowledge. The rate of PPE use was found to be high. There was no difference between males and females in contracting COVID-19 infection.